EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN GROUP INVESTIGATION (GI) PADA MATERI SEGITIGA DAN SEGIEMPAT DITINJAU DARI ADVERSITY QUOTIENT (AQ) SMP NEGERI SE-KABUPATEN TULANG BAWANG BARAT - Irma Ayuwanti; Tri Atmojo Kusmayadi; Riyadi Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objectives of the research  were to find out: (1) which one providing better mathematics learning achievement, NHT, GI or direct learning model, (2) which one having better mathematics learning achievement, students with climbers, campers or quitters AQ, (3) in each learning models (NHT, GI and direct) which one providing better mathematics learning achievement, climbers, campers or quitters AQ, (4) in each student AQ (climbers, campers, and quitters) which one providing better mathematics learning achievement, NHT, GI or direct learning  model.This study was a quasi-experimental research. The research design used was a 3x3 factorial design. The population of research was all VII graders of Junior High Schools throughout West Tulang Bawang Regency in the school year of 2014/2015. Meanwhile the sample was taken using stratified cluster random sampling. The sample consisted of 281 students: 93 students for experiment I class, 93 for experiment II class and 95 for control class. The instruments used to collect the data were learning AQ questionnaire and  mathematics learning achievement test. From the result of research, it could be concluded as follows: (1) NHT learning model provided mathematics learning achievement better than GI learning model and direct learning model, GI learning model provided mathematics learning achievement better than direct learning model. (2) The learning achievement of the students with climbers AQ was better than that of those with campers and quitters AQ, and the learning achievement of the students with campers AQ was better than that of those with quitters AQ. (3) In NHT learning model, students with climbers and campers AQ had the same achievement, students with climbers  and campers AQ had better achievement than students with quitters AQ; qqqin GI learning model, students with climbers and campers AQ had the same achievement, students with climbers AQ categories had better achievement than students with quitters AQ, students with campers and quitters AQ had the same achievement; in direct learning model, students with climbers, campers and quitters AQ had the same achievement. (4) In climbers AQ, NHT learning modelqqq gave the same achievement as GI learning model, NHT learning model gave better achievement than in direct learning model, GI learning model gave the same achievement as direct learning model; in campers AQ, NHT learning model gave the same achievement as GI learning model, NHT learning model gave better achievement than in direct learning model, GI learning model gave the same achievement as direct learning model; in quitters AQ, NHT, GI and direct learning model gave the same achievement. Keywords: NHT, GI, Direct Learning, and Adversity Quotient (AQ).